Aspects of Seerah in the poetry of Maulana Muhammad Akram Awan (R.A) - Dr.Mubbasher Hassan Awan (Seerat Studies, 2025)
Maulana Muhammad Akram Awan (d:2017) was the Sheikh of the Silsila Naqshbandiah Owaisiah and a versatile personality. He served in various fields of life as a farmer, teacher, businessman, poet, educationist, physician, tourist, commentator, thinker, hadith commentator, commentator, writer, humorist, journalist, and politician. Research work is ongoing on every aspect of his personality. He also tried to reform mankind through poetry. As a poet, he wrote in both Urdu and traditional Punjabi. He authored seven poetry collections in Urdu: “Gard-e-Safar,” “Nishan-e-Manzil,” “Mata’-e-Faqeer,” “Aas in theJazeera,” “Deeda-e-Tar,” “Kaun Si Aisi Baat Hui Hai,” and “Soch Samundar.” His only Punjabi poetry collection is titled “Dil Darwaza.” In his poetry, he used the pen names Faqeer, Seemab Owaisi, and sometimes Ameer. The main themes of his poetry are Divine love, love for the Prophet Muhammad ﷺ, , serving humanity, political reform and humor. His poetry beautifully expresses the meanings of the Holy Qur’an, the sayings of the Prophet ﷺ (Hadith), and the Seerah of the Holy Prophet ﷺ. Like the great poets of the past, he skillfully used allusions and classical literary terms in his work. This article presents a research discussion on the salient aspects of Seerat-e-Tayyaba in his poetry.